2021
DOI: 10.1007/s40750-021-00163-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Self-rated Attractiveness Predict Women’s Preferences for Facial Masculinity? Data From an Arab Sample

Abstract: Objectives Because more attractive women may be better able to attract and/or retain masculine mates, many researchers have proposed that women who consider themselves to be more physically attractive will show stronger preferences for men displaying masculine facial characteristics. Empirical evidence for this putative association between women’s self-rated attractiveness and preference for facial masculinity has come almost entirely from studies of Western women. Thus, we investigated whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It is therefore an open question whether such associations occur in more culturally diverse samples. Indeed, a recent study of Arab women's face preferences found no evidence that Arab women who considered themselves to be particularly attractive showed stronger preferences for masculine men 20 . Moreover, some researchers have suggested that correlations between self-rated attractiveness and preferences for sexually dimorphic facial characteristics could simply be a by-product of regional variation in face preferences and self-rated attractiveness 14,17 .…”
mentioning
confidence: 96%
“…It is therefore an open question whether such associations occur in more culturally diverse samples. Indeed, a recent study of Arab women's face preferences found no evidence that Arab women who considered themselves to be particularly attractive showed stronger preferences for masculine men 20 . Moreover, some researchers have suggested that correlations between self-rated attractiveness and preferences for sexually dimorphic facial characteristics could simply be a by-product of regional variation in face preferences and self-rated attractiveness 14,17 .…”
mentioning
confidence: 96%